Development of ube candy from ube powder - Runas, Felisa Asuncion L. (2002)
BSTRACT Ube (Dioscorea alata)is an important rootcrop in the country that is also gaining popularity in other regions of the world. It is used in making favorite Filipino desserts - pastillas, halaya, jam and ice cream among others. Ube powder is an intermediate product that can also be used in making these products and other food items. It is easier to handle and has longer shelf life than raw ube. The study shows that ube powder can be made into ube candy by adding fat, sugar, milk, lecithin, and using essentially the same processing employed in chocolate manufacture. The ube candy developed in this study is composed of the following:ube powder 100%, cocoa butter substitute (CBS) 133.33%, sugar 93.33%, milk 38.3%, and lecithin 1.7% (%based on the weight of ube powder used). The physico-chemical characteristics of the product are: pH = 6.3, Aw = 0.79, TSS = 38.5%, color = 5P 5/4. The product is light violet in color and slightly in appearance. It has a slightly perceivable aroma and a perceivable flavor. The sweetness was rated as 'just right', and the texture as 'neither gritty nor smooth'. The formulation and the processing adapted in this study were determined to be repeatable at laboratory scale.